Randomised controlled trial testing the effect of cotrimoxazole prophylaxis on morbidity and mortality outcomes in breastfed HIV-exposed uninfected infants: study protocol. Issue 7 (12th July 2016) - Coutsoudis, Anna; Daniels, Brodie; Moodley-Govender, Eshia; Ngomane, Noluthando; Zako, Linda; Spooner, Elizabeth; Kiepiela, Photini; Reddy, Shabashini; Kuhn, Louise; Ramjee, Gita
Abstract : Introduction: No randomised controlled trial (RCT) has examined the efficacy of cotrimoxazole (CTX) prophylaxis in HIV-exposed uninfected (HEU) infants during the breastfeeding period, in this new era of effective prevention of mother-to-child transmission (PMTCT) prophylaxis. The efficacy of CTX prophylaxis has presently been demonstrated only in HIV-infected children. The absence of proven benefits in HEU breastfed infants associated with infectious diseases justifies an RCT as proposed. Herewith lies the rationale for conducting the proposed study. Methods: A partially blinded RCT is proposed to evaluate the efficacy of CTX prophylaxis administered from 6 weeks of age to HEU infants receiving a PMTCT regimen. A non-inferiority design will be used, randomising 1298 infants to receive CTX or not to receive CTX. Participants will be reviewed at the following time points: 6 weeks (enrolment and randomisation), 10 weeks, 14 weeks, 4 months and monthly thereafter until 12 months of age. They will be evaluated for anthropometric growth, interval illness, CTX adherence, signs and symptoms of study drug toxicity, concomitant medication use, breastfeeding status and HIV infection status. The study will compare the incidence of grade 3 and grade 4 common childhood illnesses (focusing on pneumonia and diarrhoea) and all-cause mortality until 12 months of age. In a subset of participants, we will compare grade 3 and grade 4 haemoglobin and alanine aminotransferase results as well as investigate gut integrity. Ethics and dissemination: The study has ethical approval from the University of KwaZulu-Natal Biomedical Research Ethics Committee (BFC212/13). Trial registration numbers: PACTR201311000621110 and DOH-27-0614-4728; Pre-results.